The survival of the Democratic Party outside the South: An update and reassessment. (July 2015) - Knuckey, Jonathan
Partisan change outside of the South has not been studied as extensively as in the 11 states of the Old Confederacy. Given the partisan advantage that the Democratic Party enjoys outside of the South, understanding the dynamics of party support among non-southerners appears to be important to study in its own right – not just as a point of contrast to that of the South. The goal of this article is to update and expand on one of the few pieces of scholarship to probe the reasons for the survival of the Democratic Party outside of the South. Using data from the American National Election Studies, the article concurs with these findings, that the Democratic Party has been successful in maintaining support among low income whites outside the South. However, a class-based explanation offers a partial explanation for the Democratic advantage in party identification. Ideological realignment has also expanded the Democratic base among middle and high income liberals and moderates. Overall, the findings of the article suggest that the electoral prospects of the Democratic Party outside of the South should be favourable for some time to come. The Democratic Party has not just survived outside of the South, it has prospered, and this provides a decided advantage for the party in national elections.